(untitled) (Archives of Criminology, 2008)
The aim of the article is to characterise and explain the peculiarities of crime against property in Poland by analysing data collected and published by the Polish police in the period 1924–2005. The article presents typical stages of research on crimes against property. Krzysztof Krajewski begins the discussion with an analysis of crimes against property in the People’s Republic of Poland between 1955 and 1970, stressing the importance of the October Thaw of 1956 and ‘little stabilisation’ for the analysis; then he discusses the period from 1971 to 1980 and the Gierek era, as well as the situation from 1981 to 1989, considering them as the declining period of the socialist system connected with political and economic collapse. The authoremphasises the fact that legislative changes and attempts to reclassify petty crimes were an important feature that led to a decline in crimes against property in this period. The article also explains why the general trends in the dynamics of crimes against property may differ from analogous trends for the three most important acts – theft, burglary, and robbery – the intensity and weakening of which are not the same in the different stages of the analysis. Summing up his thoughts, Krajewski claims that the pattern of crimes against property in Poland recorded in police statistics has undergone numerous transformations.